(untitled) (Academia Science Repository, 2023)
At present, in special education, along with traditional teaching methods, the use of interactive approach technologies in the formation of cognitive-speech knowledge and skills in students with hearing impairments is spreading. In this article, we propose as a technology for an interactive approach in the formation of cognitive-speech knowledge and skills in students with hearing impairments to organize lessons using visual communication tools, that is, video content, through which you can expand learning opportunities.